China’s integration in the Asia-Pacific regional economic cooperation - Wei, Junhua; Gao, Yue; Elahi, Ehsan (Frontiers in Psychology, 2022)
China is actively integrating into the process of economic cooperation in the Asia Pacific region. RCEP has come into force and China is one of the members of RCEP. Furthermore, China is applying to join CPTPP . This paper uses the GTAP model to measure the impact of RCEP and CPTPP on GDP, import and export, terms of trade, and social welfare of major economies under various scenarios, as well as the competitiveness and complementarity of RCEP and CPTPP. The results found that CPTPP with China's accession and RCEP will complement and strengthen each other, and the members of the two agreements can obtain great benefits; if both China and the US join CPTPP. Under some scenarios, China's import growth rate will be higher than that of its export, and in this way, it will transmit positive energy of growth to other nations; joining CPTPP of both China and the US that can help to reduce China's trade surplus with the US and promote the trade balance between China and US.